PRACTICAL RESEARCH ON ENHANCING STUDENTS’ CREATIVE ACTIVITY IN ORNAMENTAL ART LESSONS - Aslonova Navro‘za Hoshim qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article presents a practical study aimed at enhancing students’ creative activity in ornamental art lessons. The research investigates methods, strategies, and teaching techniques that stimulate creativity, engagement, and artistic competencies. Using project-based learning, collaborative exercises, and interactive digital tools, students were encouraged to explore, experiment, and develop original designs. Data were collected through observation, portfolio analysis, and reflective assessments to evaluate the effectiveness of these interventions. The findings indicate that structured practical activities, combined with guidance and feedback, significantly improve students’ creative motivation, aesthetic judgment, and ability to make innovative artistic decisions.